(untitled) (Research, Society and Development, 2021)
This article aims to expose the centrality of work as a founding category of social praxis models and approach education as a complex directed towards society, that is, inserted in the reproduction of social relations, in which men influence actions of other men. Understanding education as a secondary teleological, it can serve as a vehicle for maintaining the hegemonic order of capital. In bourgeois society, labor is captured in order to meet the needs of accumulating profits; to this end, education would be fundamental, since it would provide not only scientific knowledge for the production of goods, but would also be an instrument for the dissemination of bourgeois ethos. To account for these analyzes, reflecting on a possible alternative to this capitalist education, this study was characterized as exploratory and based on a bibliographic review, which occurred in theoretical references of Marxist contribution. Therefore, from the theoretical-methodological analyzes developed, it was possible to conclude that the construction of an education, in fact, emancipatory would require profound societal transformations, which would be able to overcome the most diverse processes of alienation and exploitation of men and women.